2002
DOI: 10.1111/j.1582-4934.2002.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1 as an endogenous inhibitor of angiogenesis and tumor growth

Abstract: Thrombospondin-1 (TSP-1) is a matricellular glycoprotein that influences cellular phenotype and the structure of the extracellular matrix. These effects are important components of the tissue remodeling that is associated with angiogenesis and neoplasia. The genetic mutations in oncogenes and tumor suppressor genes that occur within tumor cells are frequently associated with decreased expression of TSP-1. However, the TSP-1 that is produced by stromal fibroblasts, endothelial cells and immune cells suppresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
360
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 500 publications
(374 citation statements)
references
References 62 publications
10
360
1
3
Order By: Relevance
“…Recent evidence from our laboratory suggested that, through its unique extracellular matrix composition, the infarct border zone may serve as a "barrier" that protects the non-infarcted area from expansion of the inflammatory reaction ( Figure 7) [312]. Using a canine model of reperfused infarction we demonstrated a strikingly selective localization of TSP-1, a matricellular protein with potent angiostatic properties and a crucial role in TGF-β activation [331], in the extracellular matrix and microvascular endothelium of the ischemic border zone. Murine infarcts also had marked TSP-1 deposition in the border zone.…”
Section: The Infarct Border Zone As a Barrier Preventing Expansion Ofmentioning
confidence: 75%
“…Recent evidence from our laboratory suggested that, through its unique extracellular matrix composition, the infarct border zone may serve as a "barrier" that protects the non-infarcted area from expansion of the inflammatory reaction ( Figure 7) [312]. Using a canine model of reperfused infarction we demonstrated a strikingly selective localization of TSP-1, a matricellular protein with potent angiostatic properties and a crucial role in TGF-β activation [331], in the extracellular matrix and microvascular endothelium of the ischemic border zone. Murine infarcts also had marked TSP-1 deposition in the border zone.…”
Section: The Infarct Border Zone As a Barrier Preventing Expansion Ofmentioning
confidence: 75%
“…Figure 6 shows the effects of IGF-1 deficiency and hypertension on the hippocampal expression of the angiogenesis inhibitors Serpinf1 (PEDF), f i b u l i n -5 ( F b l n 5 ) ( S u l l i v a n e t a l . 2 0 0 7 ) , thromhospondin-1 (Thbs1) (Lawler 2002), Thbs2 (Volpert et al 1995), the potent anti-angiogenic chemokine platelet factor 4 (Pf4) (Bikfalvi 2004); vasohibin-1 (Vash1), which is a newly recognized (Takano et al 2014), Adamts1 ("a disintegrin and metalloproteinase with thrombospondin motifs 1"), which inhibits angiogenesis (Lee et al 2006) by suppressing endothelial cell proliferation; Col18a1, whose expression level impacts endostatin signaling and endothelial angiogenic capacity (Li and Olsen 2004) (endostatin, a potent inhibitor of angiogenesis, is a 20-kDa C-terminal fragment derived from type XVIII collagen); semaphorin-3F (Sema3f) (Ungvari et al 2011b;Frisbee et al 2007); tenomodulin (Tnmd) (Oshima et al 2003); brainspecific angiogenesis inhibitor 1 (Bai1; also known as adhesion G protein-coupled receptor B1 [ADGRB1]) (Nishimori et al 1997); chromogranin A (Chga), which encodes the precursor to several angiogenesis inhibitor peptides including vasostatin-1 and vasostatin-2 (Helle and Corti 2015) and maspin ("mammary serine protease inhibitor"; encoded by the Serpinb5 gene (Qin and Zhang 2010). Figure 7 shows the expression of Tnfa, whose overproduction has been causally linked to microvascular rarefaction (Frisbee et al 2014); Tgfb1, which regulates multiple aspects of the angiogenic process and contributes to hypertension-induced microvascular rarefaction in the heart (Koitabashi et al 2011); Tgfa; angiogenin (Ang, also known as ribonuclease 5), which is a potent stimulator of angiogenesis and an inhibitor of endothelial apoptosis; Edil3 (EGF-like repeats and discoidin Ilike domains 3), which encodes a glycoprotein secreted by endothelial cells that regulates apoptosis, cell migration (Zhong et al 2003) and induces cerebral angiogenesis in mice (Fan et al 2008); midkine (Mdk, also known as neurite growth-promoting factor 2 or NEGF2), which is a pleiotropic growth factor regulating cell proliferation, cell migration and promoting angiogenesis (Mashour et al 2001 [HB-GAM]), which is a pro-angiogenic growth factor that is structurally related to midkine and whose expression in the adult brain is induced by ischemia; Tymp (thymidine phosphorylase, also known as platelet-derived endothelial cell growth factor [ECGF1], which stimulates endothelial cell proliferation and induces angiogenesis in the brain …”
Section: Igf-1 Deficiency Exacerbates Hypertension-induced Cerebromicmentioning
confidence: 99%
“…Thrombospondin-1 (TSP-1), the first member identified, has been shown to be a potent inhibitor of angiogenesis and tumor progression [2]. In tumor cells, changes in the activity of oncogenes and tumor suppressor genes result in decreased expression of TSP-1 and the acquisition of an angiogenic phenotype [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%